How National Institutions Shape Skilled Immigrants' Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Felix Stumpf; Andreas Damelang; Martin Abraham; Sabine Ebensperger (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
This study provides novel insights into the institutional conditions under which skilled immigrants get hired for skilled jobs in different countries. We argue that immigrants' hiring chances depend on the interplay between institutions in sending countries, which determine the type of education that immigrants bring, and institutions in receiving countries, which shape employers' preferences for certain types of education. We develop a~research design that considers this interplay and allows us to directly compare how education from sending countries with different institutional arrangements is rated by employers in two countries with widely divergent institutional contexts of reception, Germany and England. Using harmonised factorial surveys, we simulate hiring processes and evaluate the chances of German and English employers inviting foreign-educated immigrants to interviews for jobs commensurate with their education. The survey design makes it possible to experimentally vary the institutional settings in which immigrants acquired their education in the sending country, and isolate their effect on employers' ratings. Our key finding is that immigrants from sending countries with highly standardised occupation-orientated education systems prevail in the hiring competition, irrespective of the education system in the receiving country.
Keywords: 300; Educational systems; Foreign education; Labour market; Vignette study; Vocational education and training; Bildungssysteme; Ausländische Abschlüsse; Arbeitsmarkt; Vignettenstudie; Berufliche Ausbildung